The Influence of Work Environment and Facilities and Infrastructure on Teacher Performance in Vocational High Schools - Wijaya, Ayu; Selamat, Selamat (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
To achieve optimal employee performance, special attention must be given to all factors that influence performance, including environmental factors and infrastructure. At Tunas Wiyata Vocational School, the work environment is not yet considered conducive, leading to delays in the teaching and learning process, resulting in suboptimal performance of teachers and staff. Additionally, some teachers have not yet utilized the available facilities and infrastructure effectively. Infrastructure at Tunas Wiyata Vocational School also faces various challenges, such as poor building conditions, inadequate availability of study room equipment, and office spaces that do not meet expectations. Furthermore, there is a limited supply of teaching media and aids necessary for diverse teaching methods that adapt to classroom needs. This study aims to examine: 1) The influence of the work environment on employee performance, 2) The influence of infrastructure on employee performance, and 3) The combined influence of the work environment and infrastructure on employee performance at Tunas Wiyata Vocational High School. The research uses a quantitative descriptive method, analyzing numerical data to understand relationships between variables within a population. Simple and multiple regression analyses were used, with 49 respondents participating in the study. Based on the research results, it was found that the work environment and infrastructure variables influenced the performance of SMK Tunas Wiyata teachers, both partially and simultaneously.